UPAYA MENINGKATKAN KETERAMPILAN BAHASA INGGRIS PESERTA PENGAYAAN BAHASA BEASISWA LPDP DI UPT BAHASA DAN BUDAYA ITS SURABAYA - Ester Widawati Tedjo; Sekar Kirana Syaifani (Universiitas Pamulang, 2021)
ABSTRACT Proficiency in English is a requirement for admission and graduation in higher education in Indonesia as well as in many other countries. This ability is usually shown by scores on English language proficiency tests such as TOEFL and IELTS. To help LPDP Affirmation scholarship awardees improve their English language skills and achieve target scores in TOEFL ITP or IELTS tests, LPDP provides English Language Enrichment training programs. Institut Teknologi Sepuluh Nopember (ITS) Surabaya is one of the State Universities appointed as the organizer of the Language Enrichment program for the TOEFL ITP which is done by the Center for Languages and Cultures (CLC) of ITS. This community service activity was carried out in the Language Enrichment training group which lasted three months at the CLC of ITS. During the training, observations were made through the learning process and review exercises to find out aspects of English skills that generally need to be improved. Observations were strengthened by responses to questionnaires and interviews showing that the trainees actually had mastered the basics of English grammar, but their Listening and Reading skills were relatively low. This can be due to the lack of frequent use of English in their daily activities. As language is a skill, its frequent use will make a person have a better ability in the language. Participants also felt the importance of improving writing skills, especially academic writing in the Language Enrichment program. Based on these findings, a package of Practice Test questions was made with additional Test of Written English (TWE) items, as practice material to prepare for the TOEFL ITP test. Keywords: English Proficiency, Language Enrichment Program, and TOEFL ITP ABSTRAK Kemampuan Bahasa Inggris merupakan persyaratan untuk penerimaan dan kelulusan dalam pendidikan tinggi di Indonesia maupun di banyak negara lain. Kemampuan ini biasanya dinyatakan melalui skor tes kemampuan Bahasa Inggris seperti TOEFL dan IELTS. Untuk membantu penerima beasiswa LPDP Afirmasi meningkatkan kemampuan Bahasa Inggris dan mencapai skor target dalam tes TOEFL ITP atau IELTS, LPDP menyediakan program pelatihan Pengayaan Bahasa Inggris. Institut Teknologi Sepuluh Nopember (ITS) Surabaya adalah salah satu PTN yang ditunjuk sebagai penyelenggara program Pengayaan Bahasa untuk TOEFL ITP melalui UPT Bahasa dan Budaya ITS. Kegiatan PKM ini dilaksanakan pada kelompok pelatihan Pengayaan Bahasa yang berdurasi 3 bulan di UPT Bahasa dan Budaya ITS. Selama pelatihan dilakukan pengamatan melalui proses pemelajaran dan review exercise untuk mengetahui aspek keterampilan Bahasa Inggris yang secara umum perlu ditingkatkan pada peserta. Hasil pengamatan diperkuat oleh tanggapan pada kuesioner dan wawancara menunjukkan bahwa peserta pelatihan sebenarnya telah menguasai dasar-dasar tatabahasa Inggris, namun keterampilan Listening dan Reading relative agak rendah. Hal ini dapat disebabkan oleh kurang seringnya penggunaan Bahasa Inggris dalam aktivitas sehari-hari. Bahasa merupakan suatu keterampilan sehingga penggunaan yang makin sering akan menjadikan seseorang memiliki kemampuan makin baik dalam bahasa tersebut. Peserta juga merasa pentingnya peningkatan kemampuan menulis khususnya academic writing dalam program Pengayaan Bahasa. Berdasarkan temuan tersebut disusun satu paket soal Practice Test dengan tambahan soal Test of Written English (TWE), sebagai materi latihan untuk mempersiapkan diri mengikuti tes TOEFL ITP.Kata Kunci: Kemampuan Bahasa Inggris, Program Pengayaan Bahasa, dan TOEFL ITP